The Densification Process of Wood Waste - Krizan, Peter (De Gruyter, 2015)
This book examines the very current issue of wood waste treatment to a solid biofuel for energy recovery. The book is dedicated to research in the densification processes of wood waste and its mathematical description for uniaxial densification into compact biofuels - briquettes.This monograph, derived from an experimental research of densification process in laboratory conditions and also in real technologies in practice, provides a thorough understanding of the influencing parameters impact during densification of wood waste into solid biofuel. The book shows the experimental strategy to determine the effects of individual parameters and specifies their impact on the resulting density of the briquettes. The publication also defines the level of importance of the results in terms of optimization of the densification machine's pressing chamber. Using a designed mathematical model, which was a result of experimental research and which can serve to predict the density of briquettes for some predefined densification conditions and can aid in the design of densification machines, the author has made this topic accessible beyond his discipline, biofuels producers and the academic community.